PERAN UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI SEBAGAI LOKOMOTIF PERUBAHAN SOSIAL (Studi Visi Lembaga dan Paradigma Transintegrasi) - Fridiyanto, Miftahul Khairani (Pascasarjana UIN Sumatera Utara, 2020)
Abstract: the purpose of this study was to explore the roles of Islamic State University Sulthan Thaha Saifuddin Jambi in transforming society, especially in Jambi Province. The research design was qualitative in casestudy. I analysed the Rector Speech, news, documentation, observation and interviews. I studied four major themes related to Islamic State University Sulthan Thaha Saifuddin Jambi those are moderate spirit, Islamic entrepreneurship, locomotive for social change and Transintegration paradigm. The research findings those are moderate spirit is an inclusive vision in building a peacefull society, entrepreneurship based on Islamic teachings vision is an effort to make the academic activities can be usefull economically and encourage the welfare community, locomotive for social change vision is a concept to be a pioneer in building knowledge for humanity. Then Transintegration paradigm is a philosophy and practice to make a melting point for many field disciplines. Key words: UIN Sulthan Thaha Saifuddin, Moderate, Islamic entrepreneurship, Transintegration